(untitled) (Research, Society and Development, 2022)
The present study assesses the shear strength of Polyether Ether Ketone (PEEK) and Zantex to thermopolymerizable acrylic resin (TAR) with different surface treatments. To this end, 100 test specimens were produced and divided into two groups: G1(PEEK + TAR) and G2 (Zantex + TAR). Each group was subdivided into the subgroups A, B, C, D and E (n=10) according to surface pre-treatment: A: TAR + PEEK/Zantex without surface treatment (control); B: TAR + PEEK/Zantex treated with Palabond; C: TAR + PEEK/Zantex blasted with aluminum oxide (Al2O3) of 125 µm; D: TAR + PEEK /Zantex treated with Al2O3 of 125 µm + Palabond; and E: TAR + PEEK/Zantex prepared with groove-shaped retentions. The structures were tested in a Universal testing machine EMIC DL2000. Two-way variance analysis showed significant difference between materials and surface treatments (p < 0.001). Multiple comparisons were done with Tukey’s test and failure modes were analyzed with the G test. Statistical analysis showed that Zantex outperformed PEEK for most treatments and showed similar performance in the subgroups treated with Al2O3. Within the PEEK group, the use of grooves and Palabond combined with blasting showed the best results; in the Zantex group, the best results were obtained with Palabond and Palabond combined with blasting. Regarding failure modes, PEEK showed only adhesive failures and Zantex’s failures were dependent on treatment. Therefore, the surface treatment method applied to the polymers studied here contribute to the material’s adhesion to acrylic resin.